2020
DOI: 10.1177/1360780420957036
|View full text |Cite
|
Sign up to set email alerts
|

Balancing Time – University Students’ Study Practices and Policy Perceptions of Time

Abstract: A particular concern in Danish higher education policy is how much time students spend studying, often addressed as ‘study intensity’ (defined as number of hours per week spent studying). This article discusses this concept and explores how students perceive the time they spend studying. We draw on ethnographic fieldwork, interviews and workshops among second-year students at four study programmes at a Danish research-intensive university: two in natural sciences, one in humanities, and one in social sciences.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 24 publications
0
8
0
1
Order By: Relevance
“…In England, for example, an implicit contrast is drawn between those students who work hard and are thoroughly deserving of their degree outcome and others who have not shown such commitment and yet have been unfairly rewarded with a 'good degree' as a result of 'grade inflation' (Brooks, 2018a). Similarly, in Denmark, the figure of the 'lazy' student has been used as a foil for introducing a range of reforms intended to encourage students to progress through their studies at a faster pace (Brooks, 2019;Ulriksen and Nejrup, 2020) while, across Europe more generally, reforms associated with the Bologna Process have sought to increase the 'efficiency' with which students move through their HE, with implied consequences for how hard they are expected to work (Nielsen and Sarauw, 2017). It is thus possible that such discourses serve to underline the expectation of hard work but also, through the assertion that some students are lazy, provoke a reaction in which individuals are at pains to stress their hard-working nature.…”
Section: Common Constructions Of Studentsmentioning
confidence: 99%
“…In England, for example, an implicit contrast is drawn between those students who work hard and are thoroughly deserving of their degree outcome and others who have not shown such commitment and yet have been unfairly rewarded with a 'good degree' as a result of 'grade inflation' (Brooks, 2018a). Similarly, in Denmark, the figure of the 'lazy' student has been used as a foil for introducing a range of reforms intended to encourage students to progress through their studies at a faster pace (Brooks, 2019;Ulriksen and Nejrup, 2020) while, across Europe more generally, reforms associated with the Bologna Process have sought to increase the 'efficiency' with which students move through their HE, with implied consequences for how hard they are expected to work (Nielsen and Sarauw, 2017). It is thus possible that such discourses serve to underline the expectation of hard work but also, through the assertion that some students are lazy, provoke a reaction in which individuals are at pains to stress their hard-working nature.…”
Section: Common Constructions Of Studentsmentioning
confidence: 99%
“…Scholars have also noted the shame that can arise from a perceived failure to meet new time imperatives (Shahjahan, 2020). Although the majority of work in this area has focused on staff rather than students, a small number of studies, conducted in countries where students have historically had some discretion about the length of their studies, have shown how students have come under increased pressure to complete their degrees at a faster pace (Nielsen and Sarauw, 2017; Ulriksen and Nejrup, 2020).…”
Section: Introductionmentioning
confidence: 99%
“…Empirical examinations of the impact of these reforms have suggested that students feel they are sometimes restricted to a superficial and instrumental engagement with their studies, choosing 'safe routes' through their studies, to maximise their chances of passing their exams and completing their studies in the required time (Nielsen and Sarauw, 2017;Sarauw and Madsen, 2020). Moreover, there is often a poor match between how 'study time' is understood within policy and by students themselves (Ulriksen and Nejrup, 2021).…”
Section: Denmarkmentioning
confidence: 99%